2015
DOI: 10.1111/jopr.12376
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Disilicate Restorations Fatigue Testing Parameters: A Systematic Review

Abstract: The studies reviewed showed a level of heterogeneity, as testing parameters were considered through different setups. The current study demonstrated that various setting of the testing parameters and having a lack of testing standardization has likely led to inconsistency in the reported results. The obvious heterogeneity in the setting of testing variables-especially the magnitude of load and number of cycles applied-made it impractical to run direct comparisons between the reviewed studies. Therefore, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
117
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 97 publications
(192 reference statements)
2
117
0
5
Order By: Relevance
“…Differently, as regards FDPs, the cumulative survival rates at 5 years ranged from 75% to 100% in vitro [28, 29] while the equivalent clinical rate was 78.1% [26]; long-term laboratory investigations simulating more than 10 years of service showed 70% survival rate [30], comparable to the in vivo cumulative survival rate of 70.9% after 10 years of function [26]. The sound level of agreement between in vitro and in vivo data confirmed that laboratory investigations could represent a good simulation of the clinical scenario; nonetheless, this conclusion has to be considered only indicative, since the amount of data is not large enough to indicate consolidated clinical guidelines [24]. …”
Section: Mechanical Testing and Fracture Resistancementioning
confidence: 88%
See 4 more Smart Citations
“…Differently, as regards FDPs, the cumulative survival rates at 5 years ranged from 75% to 100% in vitro [28, 29] while the equivalent clinical rate was 78.1% [26]; long-term laboratory investigations simulating more than 10 years of service showed 70% survival rate [30], comparable to the in vivo cumulative survival rate of 70.9% after 10 years of function [26]. The sound level of agreement between in vitro and in vivo data confirmed that laboratory investigations could represent a good simulation of the clinical scenario; nonetheless, this conclusion has to be considered only indicative, since the amount of data is not large enough to indicate consolidated clinical guidelines [24]. …”
Section: Mechanical Testing and Fracture Resistancementioning
confidence: 88%
“…Several laboratory studies investigated the fatigue resistance of lithium disilicate single crowns (SCs) and fixed dental prostheses (FDPs) to evaluate experimental designs and testing parameters [2024]. Different laboratory variables were proved to influence the fatigue resistance of lithium disilicate restorations, such as magnitude of load, number of cycles, abutment and antagonist material, wet environment, and thermocycling; conversely, chewing frequency, lateral movements, and aging technique were considered not influential factors [23].…”
Section: Mechanical Testing and Fracture Resistancementioning
confidence: 99%
See 3 more Smart Citations